UTILIZATION OF COMPUTER TECHONOLGY-BASED VIDEO (SCHOOL TUBE) AS LEARNING MEDIA - Ilham, Muhammad; Nurviani, Rahima; Maseela, Hunadee (Perspektif Ilmu Pendidikan, 2024)
The utilization of technology in digital era has been beneficial for all aspects of human live including education. Technology is also used as the problem solvers and solutions for educational problems faced by teachers and students in schools. Based on that situation, this research proposed to analyze and discover the impact of School Tube utilization as the learning media at Madrasah Aliyyah Negeri (MAN) 1 in Lhoksemwe. This qualitative research used a descriptive approach and employed two data collection techinques that are interview and observation. The respondents of this research were teachers and school administrators at MAN 1 in Lhokseumawe. This research found that the utilization of SchoolTube at MAN 1 Lhokseumawe has positive impact to help students in learning their subjects. It directs students to learn independently that promotes autonomous and asynchronous learning model. Besides that, Shool Tube also helps teacher in providing materials for students to learn when the teachers need to attend their administrative duties outside the classroom. On the contrary, some teachers were still found not proficient in using this media. Moreover, as a free learning media, School Tube still has limitation access, so the students could not use it outside the school compound. Thus, it is suggested to the school authorities to train and enhance teachers’ ability through workshop in using School Tube and other audiovisual application as learning media.